How to lead when you're not in charge : leveraging influence when you lack authority - Scroggins, Clay (Zondervan, 2017)
"Are you letting your lack of authority paralyze you? One of the greatest myths of leadership is that you must be in charge in order to lead. Great leaders don't buy it. Great leaders lead with or without the authority and learn to unleash their influence wherever they are. With practical wisdom and humor, Clay Scroggins will help you nurture your vision and cultivate influence, even when you lack authority in your organization. And he will free you to become the great leader you want to be so you can make a difference right where you are. Even when you're not in charge."--